Investigating the impact of leadership on resistance to change - Sarıibrahım,Mehmet Akif (My University, 2008)
In recent years, organizations have gone through dramatic changes, including flatter and looser structures, downsizing, and horizontal approaches to information flow. On the other hand, these changes are due to rapid technological developments, global competition, and the differencing structure of the workforce, also these organizational transformations and innovations are triggered by interventions, such as total quality management and business process re-engineering. The successful organization differs in the way they conduct environmental assessment, link strategic and operational change, manage their human resources, and manage coherence in the overall process of change. In fact they differ in the way they lead change. In this process there is a natural reaction to change that is called “Resistance to Change” on employees. Even if there are so many researches to solve this reaction, it is not so practically possible to remove it totally. Transformational leaders define the need for change, create new visions, mobilize commitment to those visions, and ultimately change the structure of organization. Organizations became more adaptive with their change vision and strong commitment. Naturally people who work with transformational leaders should have less resistance to change than others The main question in this study focuses the positive effect of transformational leadership on the overcoming ‘resistance to change’. Hopefully the negative correlation between transformational leadership and ‘resistance to change’ will found. Whereas transactional leaders emphasize work standards, assignments, and task-oriented goals, and rely quite heavily on organizational rewards and punishments to influence employee performance. Both transformational and transactional leaders are active leaders; however there are so many examples about absence of leadership which is called Laises-Faire leadership. These leaders avoid decision making and taking responsibility. Consequently dynamics of change will be weakened and people who work with such a leader can easily develop resistance to change because they are unfamiliar with change. Our second hypothesis is based on this approach which is “Laissez faire leadership is positively related to resistance to change”. To asses leadership, we used Multifactor Leadership Questionnaire (MLQ) is a short but comprehensive survey which measures a full range of leadership styles. Dimensions are Transformational Leadership, Transactional Leadership and laises-faire leadership. We conducted our research 35 private Turkish organizations, operating in OEM (Original Equipment Manufacturer) sector, which are small or medium sized (<100 employees). All these organizations are in a very strict competition with local and foreign equivalents. The management of these organizations is not generally so professional and these companies have to follow current technological developments to remain competitive. The rapid changes in the necessity and expectations of the customers and the new requirements that appears as result of change in management techniques enforces OEM’s to relevant adaptations. This enforcement for change affects the OEM’s substantially more than others due to limited resources and non-professional management. We selected this sector to test our hypothesises due to its dynamic and active structure. Key Words: Leadership, Change, Transformational Leadership, Resistance to Change, OEM KONU: LIDERLİĞİN DEĞİŞİME DIRENÇ ÜZERİNDEKİ ETKİSİNIN ARAŞTIRILMASI

Günümüzde organizasyonların yapılarında personel sayısının azaltılması, hiyerarşik yapıdaki değişimler, bilği akışının değişmesi gibi pek çok yenilik göze çarpmaktadır. Teknolojik gelişmeler, işgücü yapısının değişmesi ve küresel rekabet bu değişimlerin itici gücünü oluşturmaktadır. Öte yandan organizasyonlar toptan kalite yönetimi , iş süreçlerinin yenilenmesi gibi yeni yaklaşımlarla beraber bir dönüşüm ve yenilenme sürecine girmişlerdir. Başarılı organizasyonların farklılığı çevrelerini değerlendirmelerinden, stratejik ve operasyonel değişimi birbirlerine bağlamalarından, insan kaynaklarını yönetişlerinden, değişim sürecinin tamamına uyum sağlamalarından kısaca değişime kılavuzluk etmelerindeki farklılıktan kaynaklanır. Bu değişim süreci esnasında tamamen doğal bir tepki olarak değişime direnç oluşmaktadır. Değişime direnci gidermeye yönelik çok sayıda yöntem ve araştırma bulunmasına rağmen bu tepkiyi tamamen kaldırmak mümkün görünmemektedir. Dönüştürücü liderler değişim ihtiyacını tanımlayabilen, yeni vizyonlar yaratabilen ve bu vizyonları doğrultusunda insanları örgütsel değişime yönlendirebilen liderlerdir. Liderdeki bu değişim vizyonu ve kararlılığı örgütsel yapının değişim sürecine daha uyumlu olmasını sağlar. Doğal olarak dönüşümcü liderler ile çalışan bireylerde değişime direncin daha az olması beklenir. Bu çalışmanın esas amacıda dönüşümcü liderliğin değişime dirence yok etmedeki olumlu etkisini bulmaktır. Yani değişime direnç ile dönüşümcü liderlik arasında ters orantı bulunması beklenmektedir. Buna karşılık yönetsel liderler iş standartlarını, hedef odaklı görevleri vurgulayan ve çalışan performansını etkilemek için ödül ve cezaya dayanan liderlerdir. Yönetsel liderler ve dönüşümcü liderler aktif liderlerdir. Ama yinede hayatta liderliğin olmadığı(laises-faire) durumlara ilişkin örnekler çoktur. Bu tarz liderler karar almaktan, sorumluluk üstlenmekten kaçınırlar. Sonuç olarak bu tarz liderlerin bulunduğu işletmelerde değişim dinamiklerinin zayıflar ve çalışanlarda sürekli stabil durum nedeniyle kolaylıkla değişime direnç durumu belirginleşir. İkinci hipotezimiz bu yaklaşımın üzerine geliştirilmiştir: Liderliğin yokluğu değişime dirençle doğru orantılıdır. Liderliği ölçmek için Bass ve Avolio’nun Çoklu faktör Liderlik Anketi (Multifactoral leadership Qestionnaire) kullanılmıştır. Bu anket, dönüşümcü liderlik, yönetsel liderlik ve liderliğin yokluğu boyutlarını içerir. Araştırmamızın uygulaması makine üreticisi (OEM) sektöründe otuzun beş firma ile yapılmıştır. OEM sektörü genellikle küçük ve orta boy işletmelerden (çalışan sayısı <100) oluşmaktadır. Profesyonel bir yönetim anlayışına sahip olmayan bu şirketler çekirdekten yetişme şirket sahipleri tarafından yönetilmektedirler. Şirketlerin rekabetçi kalabilmeleri, en son teknolojiyi takibi gerektirmektedir. Teknolojideki ve müşteri isteklerindeki hızlı değişim makine üretici firmaları hızlı bir değişim sürecine zorlamaktadır. Ancak sahip olunan kaynakların yetersizliği ve profesyonel bir yönetim anlayışına sahip olmamaları sebebiyle değişim sürecinden diğer firmalara göre daha çok etkilenmektedirler. Makina üreticisi sektörü sahip olduğu bu dinamik yapı nedeniyle bu araştırmada tercih edilmiştir. derlik, Değişim, Dönüşümcü liderlik,Değişime Direnç ,OEM
Keywords: Liderlik